Persuasive toothpaste container as a fun motivator of children's dental care habits through the use of persuasive technology / Elly Johana Johan ... [et al.] - Johan, Elly Johana; Othman, Jamal; Wan Mohammad, Wan Anisha; Mohd Mydin, Azlina Mohd Mydin (Unit Penerbitan JSKM, 2022)
Most of the parents are facing difficulties in persuading or motivating their kids especially those age 2 to 5 years old to brush their teeth regularly. Technology can be used as influential tools to persuade the children. Realizing the importance of hygiene and oral health care through tooth brushing activities, as well as the potential of persuasive technology in instilling motivation without coercion, this research aims to encourage children (2-5 years) to brush their teeth in a fun way through the adaptation of the persuasive technology. Personalization, liking, and cooperation are three persuasive principles adapted from persuasive system design to encourage children (2-5 years) to brush their teeth in a fun way. Using a do-it-yourself (DIY) approach with household items such as a toothbrush, different flavours of toothpaste, a piping cake container, and nozzles to persuade children to practise good dental hygiene habits. This study's solution idea assumes that motivated children who maintain oral hygiene by brushing their teeth in a fun way on a consistent basis can naturally form self-discipline. Personalization, liking, and cooperation principles used in fun tooth brushing have a positive impact on developing children's discipline toward dental care habits